Pengaruh Model Pembelajaran dan Gaya Belajar Terhadap Keterampilan Berpikir Kritis dan Berpikir Kreatif - Yuntawati, Yuntawati; Aziz, Lalu Abdul (Media Pendidikan Matematika, 2024)
This research aims to find out how the factors of the PjBL and PBL learning models, as well as learning styles, kinesthetic and visual, the development of critical and creative thinking skills in students can influence and interact with each other in the educational context. The research used two classes with a total of 20 students in each class who were randomly selected. After the experiment was completed, critical thinking skills and creative thinking skills were measured. Hypothesis testing in this study used 2-way Manova multivariate covariance analysis. For each assumption test, a significance level of 5% is used. Statistical analysis techniques were carried out using the Statistical Package for Social Science (SPSS) data processor for Windows. The results of data analysis show a sig value. for Pilla's Trace, Wilks'Lambda, Hotelling'Trace, Roy's Lest Root for learning models and learning styles is greater than 0.05 which means it is not significant, then Ho is accepted. So there is no significant difference in critical thinking skills and creative thinking skills from the PjBL & PBL learning models and the kinesthetic & visual learning styles applied. While the interaction model and learning styles are smaller than 0.05, which means they are significant, then Ho is rejected. Thus, it can be concluded that there is an interaction effect between learning models and learning styles on critical thinking skills and creative thinking abilities.